2022
DOI: 10.1017/s0950268822000607
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the incidence of hospitalisation for non-invasive pneumococcal pneumonia in the Norwegian population aged 50 years and older

Abstract: The purpose of this study was to estimate simple measures of the burden of non-invasive pneumococcal pneumonia (PnPn) hospitalisations in those aged 50 years and older (50+) in Norway. We conducted a retrospective register-based study and used discharge codes from the Norwegian Patient Register (NPR). We identified episodes of non-invasive PnPn in 2015 to 2016 and predicted its incidence from 2015 to 2019 based on the trend found in notified invasive pneumococcal disease cases. Overall, we identified 45–46 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…CAP inpatient estimates were based on hospital discharge data from the Norwegian Patient Register (NPR). 18 CAP was defined as a first-listed discharge diagnosis of pneumonia according to the listed ICD10-codes. Episodes per person were defined as one or several admissions for CAP within the same 30 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAP inpatient estimates were based on hospital discharge data from the Norwegian Patient Register (NPR). 18 CAP was defined as a first-listed discharge diagnosis of pneumonia according to the listed ICD10-codes. Episodes per person were defined as one or several admissions for CAP within the same 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Episodes per person were defined as one or several admissions for CAP within the same 30 days. Further details and description of the data compilation can be found elsewhere 18 In line with the Swedish study, we assumed that 30% of the cases would be caused by pneumococci. 19 Norwegian CAP data including only noninvasive episodes from 2015 was used to estimate the incidence of PnCAP.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the data offered by another study in 2015 on the impact of four vaccine-preventable diseases in older adults in Spain [5] and Italy, where, despite reductions in pneumococcal disease-related expenditures following the introduction of PCV13, there continues to be an important economic burden associated with pneumococcal disease [21]. In Norway, a recent study indicated that the burden of noninvasive pneumococcal pneumonia hospitalization had a substantial impact on the health and health care use of the 50+ population in Norway, despite the childhood immunization program [22].…”
Section: Discussionmentioning
confidence: 99%